PERANAN INTERKORELASI BUTIR TERHADAP KOEFISIEN RELIABILITAS CRONBACH ALPHA DAN KUDER-RICHARDSON - Naga, Dali Santun (Jurnal Kependidikan, 2004)
Abstract Alpha Cronbach and Kuder-Richardson reliability coefficients are also called lower bound coefficient. From score structure, it is found that respondent score variance and item score variances are together related to the covariance of the item intercorrelations which in turn is also related to the item equivalences within the test. A deviation from these equivalences can disrupt this reliability coefficient and hence it is called lower bound coefficient.